Pengaruh Return On Equity (Roe), Debt On Equity Ratio (Der) Dan Net Profit Margin (Npm) Terhadap Return Saham (Studi Empiris Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia 2016-2020) - Ingra Sovita; Meizi Lidia Rosa (LPPM Universitas Dharma Andalas, 2022)
This study aims to analyze the Effect of Return On Equity (ROE), Debt On Equity Ratio (DER) and Net Profit Margin (NPM) on Stock Return (Empirical Study on Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange 2016-2020) . This type of research is a quantitative study with a population of Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange 2016-2020. The data used are in the form of annual financial statements of companies that are sampled in the study with a period of 5 years. The sample of this research was determined by purposive sampling method in order to obtain 80 companies. The type of data used is secondary data obtained from the website of each company and www.idx.co.id. The analytical method used is descriptive statistics, classical assumption test, multiple linear regression and hypothesis testing using SPSS version 23. The partial results show that return on equity has a significant effect on stock returns, debt to equity ratio has a significant effect on stock returns, and net profit margin has a significant effect on stock returns